2008
DOI: 10.1111/j.1600-6143.2008.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Costimulatory and Interleukin 2 Receptor Blockade on Regulatory T Cells in Renal Transplantation

Abstract: Regulatory T cells (Treg) are critical regulators of immune tolerance. Both IL-2 and CD28-CD80/CD86 signaling are critical for CD4+CD25+FOXP3+ Treg survival in mice. Yet, both belatacept (a second-generation CTLA-4Ig) and basiliximab (an anti-CD25 monoclonal antibody) are among the arsenal of current immunotherapies being used in kidney transplant patients. In this study, we explored the direct effect of basiliximab and belatacept on the Tregs in peripheral blood both in the short term and long term and in kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
131
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(149 citation statements)
references
References 28 publications
14
131
1
1
Order By: Relevance
“…14 It is noteworthy to differentiate our results from the belatacept phase III trial, which showed higher rates of early endarteritis (18% versus 4%) and slightly less DSA (4% versus 7%) but superior renal function and comparable graft survival through 5 years in patients treated with belatacept versus cyclosporin, respectively. [24][25][26] Another study indicated that patients treated with belatacept had more T-regulatory cells in biopsies during rejection compared with patients treated with calcineurin inhibitor, 27 suggesting that belatacept may ease recovery from acute rejection by selective immune regulation. In contrast, most patients in our cohort were on calcineurin inhibitors, and endarteritis unresponsive to anti-T cell therapy was a poor prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…14 It is noteworthy to differentiate our results from the belatacept phase III trial, which showed higher rates of early endarteritis (18% versus 4%) and slightly less DSA (4% versus 7%) but superior renal function and comparable graft survival through 5 years in patients treated with belatacept versus cyclosporin, respectively. [24][25][26] Another study indicated that patients treated with belatacept had more T-regulatory cells in biopsies during rejection compared with patients treated with calcineurin inhibitor, 27 suggesting that belatacept may ease recovery from acute rejection by selective immune regulation. In contrast, most patients in our cohort were on calcineurin inhibitors, and endarteritis unresponsive to anti-T cell therapy was a poor prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs. [24][25][26] Taking into account the potential impacts of basiliximab on Treg function and the well-accepted fact that a complex network of cytokines, cellular receptors, and immune cell subsets resulting in the initiation and maintenance of aGVHD, we speculated that the blockade of multiple effector pathways may ultimately be necessary. To our knowledge, our study is the first prospective, multi-center clinical trial to develop a combined inflammatory cytokine inhibition therapy for SRaGVHD by using basiliximab and etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of this treatment to prevent acute rejection is similar to rabbit antithymocyte globulin treatment with fewer side effects (Soulillou et al, 1990). Nowadays it's clearly demonstrated that treatments with anti-IL2R associated with cyclosporin A and steroids ameliorate the survival of the graft and decrease opportunistic infections, but nevertheless with a little more acute rejection (Brennan et al, 2006) and a decrease of Tregs in periphery (Bluestone et al, 2008). Alentuzumab (Campath-1H), a humanized rat monoclonal antibody, binds CD52, a glycoprotein expressed by T and B lymphocytes, monocytes and granulocytes (Xia et al, 1993).…”
Section: The Use Of Monoclonal Antibodies: T Cell Depletion and Blockmentioning
confidence: 98%
“…Treatment with Belatacept permit to have effective immunosuppression, superior renal function and reduced incidence of chronic allograft nephropathy than in patients treated with cyclosporin A . Treatments with Belatacept have no adverse effects on Tregs and even improve their infiltration in the graft (Bluestone et al, 2008). A recent study has tested the immunoregulatory effect of selective CD28 blockade on kidney and heart allograft in primates (ref).…”
Section: The Use Of Monoclonal Antibodies: T Cell Depletion and Blockmentioning
confidence: 99%